Aprender brincando: contribuições de um projeto de colaboração entre professores de educação física e alfabetizadores - Barros, Leonardo Augusto D´almeida (2011)
The present research brings up possibilities of interaction among teachers of different disciplines, seeking to attend the main actors of education, the students , at the best way possible. From the mean objective, which is the contribution of the project Playing with letters and words for learning of 1st year of Fundamental School children?, and specifics objectives, analyze motor and written difficult presented by students during the project, and student s motor and writing progress during the project, a field research has been made with students from 1st year of Fundamental School, analyzing the development at motor, reading and writing learning from collaborative activities between literacy teacher and physical education teacher. This research, characterized as an intervention-research, of qualitative nature, had an exploratory character as it started to look for systemizing collaborative practices of teachers. Classroom and court activities were realized with the data from students development from writing activities, court activities and continuous evaluations of writing and motor development from analyses boards. At the end were analyzed seven students that had more difficult, whether writing or motor, verifying their development. Finally, this research has proposed concrete changes in thepossibilities of students in every project, whether motor or written,early in the project, we got seven students in pre-syllabic or syllabicstage worthless, and no case registered at the end. Motor under review, significant changes also analyzed, in which students whohad motor difficulties such as walking sideways, backwards orjumping on one leg at the end of the project had advanced concepts